A CONSULTA POPULAR COMO ESTRATÉGIA DE PLANEJAMENTO PARA O DESENVOLVIMENTO SÓCIOECONÔMICO REGIONAL - SIEDENBERG, DIETER R.; ALLEBRANDT, SÉRGIO L.; SOUZA, JOSÉ D. D.; RI, MARLENE K. D.; DUTRA, VIVIANE B.; PETERSEN, LETÍCIA L.; MALETZ, EDSON A.; GIANLUPPI, NÁDIA (Salão do Conhecimento, 2013)
Resumo